Toward Mass Production of CVD Graphene Films. Issue 9 (16th September 2018) - Deng, Bing; Liu, Zhongfan; Peng, Hailin
Abstract: Chemical vapor deposition (CVD) is considered to be an efficient method for fabricating large‐area and high‐quality graphene films due to its excellent controllability and scalability. Great efforts have been made to control the growth of graphene to achieve large domain sizes, uniform layers, fast growth, and low synthesis temperatures. Some attempts have been made by both the scientific community and startup companies to mass produce graphene films; however, there is a large difference in the quality of graphene synthesized on a laboratory scale and an industrial scale. Here, recent progress toward the mass production of CVD graphene films is summarized, including the manufacturing process, equipment, and critical process parameters. Moreover, the large‐scale homogeneity of graphene films and fast characterization methods are also discussed, which are crucial for quality control in mass production. Abstract : The growth of large‐area high‐quality graphene films by chemical vapor deposition (CVD) is the key for industrial‐scale applications. Recent progress on the efforts toward the mass production of CVD graphene films is reviewed, including aspects related to fabrication process, large‐scale equipment, and critical parameters. Moreover, the issues of quality control and large‐scale homogeneity are discussed.